The Teaching of the Arabic lexicon to Spanish students: Difficulties and didactic proposals - El Khaymy, Asmaa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The lexicon is one of the most essential components in language teaching, since it plays an important role in the development of both written and oral skills. It is an element that learners must acquire and improve to achieve the desired linguistic competence. The objective of this article is to reflect on the acquisition of the Arabic lexicon as a foreign language by Spanish students, to put the finger on some semantic difficulties of Arabic and to present didactic proposals to overcome the obstacles.